THE ROLE OF ACTIVIN A AND FOLLISTATIN IN THE DIFFERENTIATION BETWEEN VIABLE INTRAUTERINE PREGNANCY FROM MISSED MISCARRIAGE AND ECTOPIC PREGNANCY - ESRAA HAMEED HUMADI AL-MAINI; ISRAA TAILB ABD AL-KADIR; RAWNAQ ALI AL-SAADI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to investigate the role of activin A and follistatin (FS) in the differentiation between viable intrauterine pregnancy from missed miscarriage and ectopic pregnancy (EP). Study Design: This was a case–control study. Setting: This study was conducted at the Department of Obstetrics and Gynecology at Al-Yarmouk Teaching Hospital, from February 2017 to October 2017. Patients and Methods: The study included 90 pregnant women, aged from 21 to 40 years old in their the first trimester attending the outpatient and inpatient clinic with single fetal pregnancy with a gestational age range between 6th and 8th weeks, they were divided into three groups; Group A: Includes 30 cases with uncomplicated pregnancies in their first trimester, Group B: Includes 30 cases diagnosed as missed miscarriages, and Group C: Includes 30 cases diagnosed as EPs. Results: There was no significant difference in the maternal age and body mass index between the three groups, β-human chorionic gonadotropin, activin A, FS, and their ratio were significantly higher in the healthy intrauterine pregnancy compared to missed miscarriage and EP. Activin A and activin A/FS ratio had an excellent ability to discriminate EP from healthy intrauterine pregnancy, while FS alone had good ability to discriminate between EP and intrauterine pregnancy. Activin A had fair ability to discriminate missed miscarriage from intra healthy uterine pregnancy, while both FS and activin A/FS ratio had poor ability to differentiate missed miscarriage and intrauterine pregnancy. Conclusion: Activin A can be used with high accuracy as a biomarker for EP and missed miscarriage, FS alone, and activin A/FS ratio is a possible biomarker, but it offers lower accuracy compared to activin A alone.